Cultivation of cherry tomato under irrigation with saline water and nitrogen fertilization - Ianne G. S. Vieira; Reginaldo G. Nobre; Adaan S. Dias; Francisco W. A. Pinheiro (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The study was carried out from August 2013 to January 2014 to evaluate growth and production of cherry tomato cultivated under irrigation with water of different salinity levels and fertilized with different nitrogen (N) doses, in experiment conducted in drainage lysimeters under greenhouse conditions, at the Center for Agrifood Science and Technology of the Federal University of Campina Grande. The statistical design was randomized blocks in a 5 x 4 factorial scheme, with three replicates, and the treatments consisted of five levels of electrical conductivity of water (0.3, 1.5, 2.5, 3.5 and 4.5 dS m-1) and four N doses (60, 100, 140 and 180 mg kg-1). Growth and production variables of cherry tomato decrease linearly from the irrigation water salinity of 0.3 dS m-1 on. The longer exposure of plants to salt stress caused the highest reductions, and the root dry matter, leaf area and the number of clusters are the most sensitive variables. The highest value of plant height at 125 days after transplantation was obtained with the N dose of 139 mg kg-1 of soil. Increasing N doses reduced the effect of salinity on cherry tomato growth at 125 days after transplantation.